A (in) adequação do tratamento jurídico aplicado ao psicopata à luz do direito penal brasileiro: entraves e lacuna normativa - Faber, Evelyn de Oliveira (My University, 2026)
This paper analyzes the legal treatment given to the psychopath and his (in)adequacy. The analysis was carried out based on the following problematic perspective: the current legal-penal treatment applied to psychopaths is consistent with the constitutional conceptions conveyed to punishment and resocialization? To answer the proposed problem, the study aimed to analyze the (in) effectiveness of the current legal treatment applied to psychopaths in the light of the ideal of resocialization. The methodology used was the literature review, qualitative and explanatory. The results showed that the psychopath does not present mental disorders, but rather an antisocial personality disorder and, due to his ability to distinguish a criminal act from a non-criminal act, should be criminally responsible for his actions. However, it is important to approach this punishment carefully, taking into account the impossibility of curing the disorder and the complexity in reintegrating individuals who suffer from this disorder to society. Moreover, it was found that merely punishing them, incarcerating them in conventional prisons and releasing them after serving their sentence, is not effective in reducing recidivism. Despite this, Brazilian legislation does not provide adequate treatment, nor is it prepared to deal with such individuals. It was concluded by the urgent need for state intervention in order to create a specific legislation for psychopaths and to allocate resources in training specialists able to more accurately identify the disorder, in addition to providing adequate treatment, through specific facilities to prevent recurrence, as well as protection of society, which ends up being hostage to such individuals. [resumo fornecido pelos autor]
O presente trabalho analisa o tratamento jurídico conferido ao psicopata e sua (in)adequação. A análise foi realizada com base na seguinte perspectiva problemática: o atual tratamento jurídico-penal aplicado aos psicopatas possui coerência com as concepções constitucionais veiculadas à pena e à ressocialização? Para responder a problemática proposta, o trabalho teve como objetivo geral analisar a (in)eficácia do atual tratamento jurídico aplicado aos psicopatas sob a luz do ideal de ressocialização. A metodologia utilizada foi a revisão bibliográfica, de cunho qualitativo e caráter explicativo. Os resultados mostraram que o psicopata não apresenta desordens mentais, mas sim um transtorno de personalidade antissocial e, devido à sua habilidade em distinguir um ato criminoso de um ato não criminoso, deve ser responsabilizado criminalmente por suas ações. No entanto, é importante abordar essa punição com cuidado, levando em conta a impossibilidade de cura do transtorno e a complexidade em reintegrar indivíduos que sofrem desse transtorno à sociedade. Ademais, constatou-se que meramente puni-los, encarcerando-os em prisões convencionais e libertando-os após o cumprimento da pena, não é efetivo na diminuição da reincidência. Apesar disso, a legislação brasileira não prevê tratamento adequado, tampouco está preparada para lidar com tais indivíduos. Concluiu-se pela necessidade urgente de intervenção estatal para fins de criar uma legislação específica para psicopatas e de alocar recursos em capacitação de especialistas capazes de identificar de forma mais precisa o transtorno, além de prover o tratamento adequado, por meio de instalações específicas para prevenção da reincidência, bem como proteção a sociedade, que acaba sendo refém de tais indivíduos. [resumo fornecido pelos autor]
Keywords: Direito penal; Distúrbios da personalidade; Responsabilidade penal; Ressocialização